Role of Exclusive Breastfeeding in Preventing Diarrhea - Hanifah Rohmah; Tisnasari Hafsah; Lulu Eva Rakhmilla (Althea Medical Journal, 2015)
Background: Breast milk has protective factors for infants’ digestive tract. Infants are vulnerable to diseases, one of which is diarrhea. This cross-sectional study was designed to determine the relation between the proportion of diarrhea in infants and the administration of exclusive breastfeeding in Jatinangor.Methods: This study was an observational study. Data on mothers with 6 months old infants were collected from Jatinangor Primary Health Center (PHC) infant records. The inclusion criteria applied were infants born in April 2012, alive, and living in Jatinangor subdistrict. One hundred and seventy one infants were recorded in April of 2012 in the PHC data. Thirty five were excluded because they were not born in April 2012. Another 45 were excluded because they were not permanent residents of Jatinangor subdistrict, while 4 infants died, and 23 had incomplete data. Therefore, only 66 infants were included as study subjects. Those infants came from 12 villages in the subdistrict of Jatinangor. Data collection was then performed using a questionnaire to the parents during the period of 21–31 October 2012.Results: From 66 infants, the proportion of diarrhea was 66.7%. Only 27.3% of all infants received exclusive breastfeeding. There was a difference in the proportion of diarrhea between infants who were exclusively breastfed and those who were not. Exclusive breastfeeding also reduced the risk of diarrhea (OR= 0.26, 95% CI 0.08–0.83).Conclusions: There is a relation between the proportion of diarrhea in infants and exclusive breastfeeding in Jatinangor. Breastfeeding has a protective effect against diarrhea in infants.Keywords: Diarrhea, exclusive breastfeeding, infants DOI: 10.15850/amj.v2n1.436